Effect of Thrombomodulin Alfa on Disseminated Intravascular Coagulation in Patients with Lung Cancer - Nakano, Kentaro (Intern Med, 2017)
OBJECTIVE: The mortality rate due to disseminated intravascular coagulation (DIC) is higher in patients with lung cancer than in those without. We examined the effect of treatment with thrombomodulin alfa (TM-α) for DIC in lung cancer patients. METHODS: Subjects were 57 patients with DIC (43 men, 14 women; mean age, 71.7 years), comprising 31 with lung cancer and 26 without. DIC patients with or without lung cancer did not differ significantly in their background characteristics. RESULTS: No significant difference was noted in the mortality rate between patients with lung cancer (61.3%) and those without (57.7%). However, the dose of TM-α was higher for survivors with lung cancer than for non-survivors (473.1 U/kg/day vs. 380.6 U/kg/day; p<0.01). Although no significant difference was noted in the DIC score between these four groups, the serum C-reactive protein level (6.9 mg/dL vs. 11.6 mg/dL; p<0.05) and prothrombin time-international normalized ratio (PT-INR; 1.10 vs. 1.52; p<0.05) were lower in survivors with lung cancer than in the non-survivors with lung cancer. The initial body temperature in non-survivors without lung cancer was lower than that in survivors without lung cancer (37.2℃ vs. 37.9℃, p<0.01), and the platelet count and the time to recovery from DIC in patients without lung cancer showed a significant negative correlation (r(2)=0.438, p<0.05). CONCLUSION: Our findings suggest that although 380 U/kg/day of TM-α is the recommended dose for DIC treatment, a higher dose may reduce the mortality rate of lung cancer patients with DIC. Furthermore, TM-α should be initiated before worsening of DIC parameters.